Occurrence of Aflatoxin B1 in Corn in Vojvodina, Republic of Serbia, Over the Last Fourteen Years (2010-2023) - Horvatović Miroslava Polovinski; Krstović Saša; Jajić Igor; Guljaš Darko; Damjanović Marko (Contemporary Agriculture)
Mycotoxins, including aflatoxins, are pervasive contaminants in crops worldwide, with aflatoxin B1 being particularly significant due to its effects on agricultural production and food safety. Serbia has a well-developed crop production sector. The increasing risk of aflatoxin contamination in certain parts of Europe, particularly the Balkan Peninsula, became evident during the 2013 outbreak. This study presents the results of 14-year monitoring (2010–2023) of corn for the occurrence of aflatoxin B1 in the Republic of Serbia. A total of 1167 samples were analyzed, of which 422 samples (36%) exceeded the limit of quantification. Among these, 183 samples were above the EU regulatory limits (EC, 2002), while 150 samples were above the regulatory limits of the Republic of Serbia. The year 2012 was particularly prominent for the high occurrence and concentration of aflatoxin B1 (AFB1) in corn, when 128 out of 132 samples tested positive for AFB1. The average concentration in all positive samples was 55±57 µg kg-1, with a maximum value of 367 µg kg-1, which exceeded the Serbian legal limit by over ten times and the EU limit by more than fifteen times. High incidence of AFB1 in analyzed samples was also in 2022, with 61% of samples exceeding the AFB1 limit of quantification. The average concentration in 2022 was 47±81 µg kg-1, with a maximum recorded value of 560 µg kg-1. The results indicate that aflatoxin B1 will remain a persistent challenge in crop production, with certain years exhibiting exceptionally high levels of contamination.